Comparative study of the biosorption of Pb(II), Ni(II) and Cr(VI) ions onto S-cerevisiae - Özer, A; Özer, D (Elsevier Science Bv, 2003)
In this study, the biosorption of Pb(II), Ni(II) and Cr(VI) ions onto inactive Saccharomyces cerevisiae was investigated as a function of initial pH, initial metal ion concentration and temperature. The Langmuir model was applied to experimental equilibrium data of Pb(II), Ni(II) and Cr(VI) biosorption depending on temperature and the maximum metal ions uptake at optimum biosorption temperature of 25 degreesC, were found to be 270.3, 46.3 and 32.6 mg g(-1), respectively. Using the Langmuir constant, b values obtained at different temperatures, the biosorption heats of Pb(II), Ni(II) and Cr(VI) were determined as -1.125, -1.912 and -2.89 kcal mol(-1), respectively. The results indicated that the biosorption of Pb(II), Ni(II) and Cr(VI) ions to S. cerevisiae is by the physical adsorption and has an exothermic nature. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: biosorption; biosorption heat; Saccharomyces cerevisiae; Langmuir isotherm